PENERAPAN ELEGANT STYLE FASHION DENGAN SUMBER IDE BENTUK ARSITEKTUR LAWANG SEWU MENGGUNAKAN TEKNIK BATIK TULIS - Fina Aulia; Salim Salim; Amin Sulistiyowati (Akademi Seni dan Desain Indonesia Surakarta, 2022)
The design of fashion in this final project aims to create a party dress design that combines the source of ideas and fashion styles that have been selected, namely elegant fashion style. The source of the idea of this design is lawang sewu. Lawang sewu is a building in the city of Semarang, Central Java, which has 600 doors and windows. The material used in this design is silk cotton with modern motifs designed according to the theme, namely Lawang Sewu. The colors of the three designs follow the 2020-2021 fashion trend, which is spirituality. Keywords: Lawang Sewu